WHIRLWIND DISASTER MITIGATION IN SUNGAI TABUK SUB-DISTRICT, BANJAR REGENCY - Putri Hilal Aulia Lasmi; Deasy Arisanty; Eva Alviawati; Karunia Puji Hastuti; Parida Angriani (JURNAL SOCIUS, 2022)
Mitigation is an adaptation in the form of efforts to prevent or protect community infrastructure and others from disasters based on an analysis of events that have occurred and losses experienced. Disaster mitigation is divided into 2: structural mitigation and non-structural mitigation. This research aimed to analyze the whirlwind disaster mitigation in Kecamatan Sungai Tabuk, Kabupaten Banjar. The method in this research is a qualitative method in which data collection uses the snowball technique. The research subjects were 12 informants consisting of stakeholders and the community, 3 of BPBD, 1 of the Dinas Sosial, 1 of Kecamatan, and seven people from the district. Data processing in this research uses source triangulation and method/technique triangulation. The data obtained were then analyzed descriptively, data collected, data reduced, data presented, and concluded. The results of the research indicate that the efforts of the government and the community regarding whirlwind disaster mitigation, both structural mitigation and non-structural mitigation, are still lacking. The lack of optimal disaster mitigation in the regions is due to the lack of coordination between stakeholders and the community and the lack of community enthusiasm for knowledge about disaster mitigation